The potential of provitamin A maize (Zea mays L.) biofortification in sub-Saharan Africa: current status, opportunities, challenges and perspectives: A review - Mudadirwa, Derek; Thokozile Ndhlela; Olakojo, Samuel Adewolo; Gonhi, Tinovonga (CAB International, 2023)
Maize is a potential crop for improving food and nutritional security for over 300 million people in sub-Saharan Africa (SSA). It is the most preferred cereal crop in SSA because of its diversified uses, taste and higher grain yield potential compared to other cereals. However, overdependence on maize-based diets without vitamin A supplementation is associated with the highest rates of vitamin A deficiency (VAD) in SSA. Vitamin A deficiency mostly affects children under the age of 5 years, pregnant and lactating women, accounting for the worst disease burden, and infant mortality in SSA. To date provitamin A maize breeding programmes of HarvestPlus partnered with CIMMYT and IITA, private seed companies and national plant breeding programmes developed at least 70 elite varieties to curb VAD in SSA. This review summarizes the potential of provitamin A maize in SSA focusing on (1) reasons why maize is a good choice for provitamin A biofortification, (2) the prevalence of vitamin A deficiency in SSA, (3) the Global Hunger Index (GHI) and extent of hidden hunger, (4) possible interventions to curb vitamin A deficiency in SSA and their applicability, (5) status of the provitamin A maize varieties released, (6) level of adoption and consumer perception of provitamin A maize-based food, (7) the impact of climate change in maize productivity in SSA and (8) the breeding methods for developing provitamin A maize-resilient genotypes to mitigate the effects of climate change in SSA.